Conversion of cheese whey into poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by Haloferax mediterranei - Pais, Joana
Haloferax mediterranei was cultivated in highly saline medium using cheese whey as the substrate for the production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate), P(3HB-co-3HV). Acid hydrolysis provided a simple inexpensive method to obtain a cheese whey hydrolysate that was used for cultivation of H. mediterranei. Batch bioreactor cultivation of H. mediterranei resulted in the production of an active biomass concentration of 7.54 g L 1 with a polymer content of 53%, and a volumetric productivity of 4.04 g L 1 day 1. Supplementation of the cultivation medium with micronutrients favored galactose consumption that was used for polymer synthesis after exhaustion of the available glucose. P(3HB-co- 3HV) with a 3-hydroxyvalerate content of 1.5 mol% was extracted from the biomass by hypo-osmotic shock. The polymer presented a molecular mass of 4.4 105, with a polydispersity index of 1.5. This work demonstrated the feasibility of using cheese whey for the production of a value-added biopolymer with high volumetric productivity, by using a glucose- and galactose-rich substrate obtained by acid hydrolysis of cheese whey. The use of H. mediterranei as the producing strain avoids the need for strict sterility due to the culture’s high salinity requirements and, also, allows for polymer extraction by simply contacting the biomass with water.